A brief outline of the use of new technologies for treating substance use disorders in the European Union - Quaglio, Gianluca; Kiefer, Falk (European addiction research, 2017)
Background: Clinicians in the field of drug addiction have started to exploit the growth of Technology-Based Interventions (TBIs). However, there is little information on how health personnel evaluate them. Methods: Semi-structured interviews were conducted among 20 European experts. Results: All of the interviewees recognised TBIs as a valuable tool to improve the management of substance-use disorders (SUDs). Most interviewees indicated that combining both traditional face-to-face therapist-patient clinic appointment with TBIs is probably the most effective method. Most interviewees agree that TBIs are valuable tools to overcome both physical and social barriers, and hence significantly facilitate the access to treatment. Poor infrastructure and lack of digital literacy are recognised as major barriers to the diffusion of these tools. Conclusions: The application of various forms of technology in SUD treatment is an interesting development for the European Union. Technical and non-technical barriers exist and impede their full exploitation.